Intersubjectivity, character and moral sentiments: the critical theory of A. Honneth and the golden rule - Testa, Italo (2008)
The text raises the question of the conditions for the possibility of intersubjectivity in the theory of recognition. An analysis of the theory of recognition formulated by Axel Honneth shows how the conflict determined by moral motivations relativizes the Habermasian premise of the linguistic understanding and brings the normative dimension back to social theory. The author returns to the pages of the Encyclopedia of Hegel to recover the objective dimension of intersubjectivity and highlights problems in Honneth’s theoretical project. He confronts both the linguistic-hermeneutic and the recognition paradigm with his pressuposition of this intersubjectivity that yet have to be established, and concludes that the theory of recognition can not explain the normative basis of intersubjectiv recognition. This theory, so Testa, describes contexts of interaction and not moral imperatives. The golden rule, especially his negative formulation is seen as a better codification of the requirement to give recognition without neglecting the experience of offenses and fight; it is seen as a better positive justification of the norms of reciprocity.